Establishment of a methodological basis of adaptive-landscape system of agriculture using Gis -technology (on the example of the northern slope of the Ili Alatau) (Eurasian Journal of Ecology, 2016)
The article discusses the principles of drawing up the soil-geomorphological and landscape maps adaptive landscape cropping system Ili Alatau northern slope of the GIS technology.
Keywords: Adaptive landscape-cropping system; geographic information systems; agro-ecological landscape; electronic database; agro-ecological classification; landscapes; electronic map.